Obtención de células madre hematopoyéticas utilizando filgrastim a 3 diferentes dosis 5, 10 y 15 microgramos en cuyes (cavia porcellus) - Sánchez Cepeda, Edison Gustavo (2015)
This research was conducted at Cotopaxi province, Latacunga Canton, Eloy Alfaro Parish, Salache Grande neighborhood in Academic Salache Experimental Center (CEASA) of the Academic Unit of Agricultural Sciences and Natural Resources (UACAREN). The objective of this study was analyze the effect of filgrastim® (r-Met-Hu-G-CSF) in the production and mobilization of hematopoietic stem cells (HSCs) in the guinea pig species, for it was conducted applying three different dosage of 5 mg, 10 mg, and 15 mg of filgrastim® compared with a control group (control) in each treatment was work with Peru line at 5 male guinea pigs, two months old, weighing 800-1000 grams. The limits specified subcutaneously for 4 consecutive days at 24 hour intervals were applied. Blood samples before each application were taken for 5 days in a row for blood borne interpretation regarding parameters….